2013
DOI: 10.1016/j.bmc.2013.04.067
|View full text |Cite
|
Sign up to set email alerts
|

20(S)-Protopanaxadiol (PPD) analogues chemosensitize multidrug-resistant cancer cells to clinical anticancer drugs

Abstract: Novel 20(S)-protopanoxadiol (PPD) analogues were designed, synthesized, and evaluated for the chemosensitizing activity against a multidrug resistant (MDR) cell line (KBvcr) overexpressing P-glycoprotein (P-gp). Structure-activity relationship analysis showed that aromatic substituted aliphatic amine at the 24-positions (groups V) effectively and significantly sensitized P-gp overexpressing multidrug resistant (MDR) cells to anticancer drugs, such as docetaxel (DOC), vincristine (VCR), and adriamycin (ADM). PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Ginsenoside Rg3 has been observed to compete with anticancer drugs for binding to ABCB1, thereby competitively inhibits drug efflux [ 18 ]. Derived from Rg3, 20( S )-protopanaxadiol (aPPD) and its analogues have also been reported to show reversal nature of ABCB1 inhibition [ 19 , 20 ]. Most ginsenosides share a dammarane-type triterpenoid saponin structure, while some minor ginsenosides isolated from P. quinquefolius with a modified steroid skeleton belong to ocotillol-type triterpenoids, of which the carbon chain at 20-position is replaced by a tetrahydrofuran ring [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Rg3 has been observed to compete with anticancer drugs for binding to ABCB1, thereby competitively inhibits drug efflux [ 18 ]. Derived from Rg3, 20( S )-protopanaxadiol (aPPD) and its analogues have also been reported to show reversal nature of ABCB1 inhibition [ 19 , 20 ]. Most ginsenosides share a dammarane-type triterpenoid saponin structure, while some minor ginsenosides isolated from P. quinquefolius with a modified steroid skeleton belong to ocotillol-type triterpenoids, of which the carbon chain at 20-position is replaced by a tetrahydrofuran ring [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PPD and its analogs have also been reported for their significant cancer cell growth inhibitory effects on human lung adenocarcinoma and oral squamous cell carcinoma. However, previous PPD studies focused on in vitro evaluations (23, 24). This study confirmed the anti-CRC effects of PPD in a dose-related manner using an in vivo xenograft nude mice model.…”
Section: Discussionmentioning
confidence: 99%
“…PPD, PPD11 and PPD12 were synthesized by our lab as previously reported [ 25 ] and prepared as a 100 mM stock solution in DMSO for in vitro studies. Verapamil (VRP), Adriamycin (ADM), Rhodamine 123 (Rho123), cisplatin (CDDP) and other chemicals were purchased from Sigma Chemical Co (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Given the extremely low toxicity of the compound, PPD is an attractive candidate as a chemo-sensitizer for treatment of MDR tumors [ 21 24 ]. To improve the effects of PPD, we previously designed and synthesized a series of PPD derivatives with aromatic substituted aliphatic amine at the 24 positions [ 25 ]. In this study, we demonstrate that PPD12, compared to its parental compound PPD and inactive compound PPD11, sensitizes ABCB1-medidated MDR cancer cells to chemotherapeutic agents in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%